2009
DOI: 10.1088/0957-4484/20/40/405206
|View full text |Cite
|
Sign up to set email alerts
|

Electrical transport properties of single undoped and n-type doped InN nanowires

Abstract: Electrical transport properties of undoped and n-type doped InN nanowires grown by molecular beam epitaxy were studied by current-voltage and back-gate field-effect transistor measurements. The current-voltage characteristics show ohmic behavior in the temperature range between 4 and 300 K. Down to about 120 K a linear decrease in resistance with temperature is observed. The investigation of a large number of nanowires revealed for undoped as well as doped wires an approximately linear relation between the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 25 publications
6
48
0
Order By: Relevance
“…8,11,25,[31][32][33][34] Moreover, it has been generally observed that there exists a very high electron concentration (∼ 1 × 10 13−14 cm −2 ) at both the polar and nonpolar grown surfaces of InN films, 19,35 and the Fermi-level (E F ) is pinned deep into the conduction band at the surfaces; 19,20,29,30 similar electron accumulation profile has also been measured at the lateral nonpolar grown surfaces of [0001]-oriented wurtzite InN nanowires. 8,11,21,22,25,36 In this regard, significant efforts have been devoted to understanding the fundamental surface charge properties of InN. 20,23,27,29,30,[37][38][39] The electron accumulation at polar InN surface has been explained by the presence of large density of the occupied In-In bond states above the conduction band minimum (CBM), 23 as well as the unusual positioning of the branch point energy (E B ) well above the CBM at the Γ-point, which allows donor-type surface states to exist in the conduction band; 20 for polar InN surface, theoretical studies agree well with experiments.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…8,11,25,[31][32][33][34] Moreover, it has been generally observed that there exists a very high electron concentration (∼ 1 × 10 13−14 cm −2 ) at both the polar and nonpolar grown surfaces of InN films, 19,35 and the Fermi-level (E F ) is pinned deep into the conduction band at the surfaces; 19,20,29,30 similar electron accumulation profile has also been measured at the lateral nonpolar grown surfaces of [0001]-oriented wurtzite InN nanowires. 8,11,21,22,25,36 In this regard, significant efforts have been devoted to understanding the fundamental surface charge properties of InN. 20,23,27,29,30,[37][38][39] The electron accumulation at polar InN surface has been explained by the presence of large density of the occupied In-In bond states above the conduction band minimum (CBM), 23 as well as the unusual positioning of the branch point energy (E B ) well above the CBM at the Γ-point, which allows donor-type surface states to exist in the conduction band; 20 for polar InN surface, theoretical studies agree well with experiments.…”
mentioning
confidence: 69%
“…8,[19][20][21][22][23][24][25][26][27][28][29][30] For example, in general, the currently reported nominally undoped InN is n-type degenerate, with the residual electron densities in the range of ∼ 1 × 10 18 cm −3 , or higher. 8,11,25,[31][32][33][34] Moreover, it has been generally observed that there exists a very high electron concentration (∼ 1 × 10 13−14 cm −2 ) at both the polar and nonpolar grown surfaces of InN films, 19,35 and the Fermi-level (E F ) is pinned deep into the conduction band at the surfaces; 19,20,29,30 similar electron accumulation profile has also been measured at the lateral nonpolar grown surfaces of [0001]-oriented wurtzite InN nanowires. 8,11,21,22,25,36 In this regard, significant efforts have been devoted to understanding the fundamental surface charge properties of InN.…”
mentioning
confidence: 99%
“…An additional error in the values of n 3d enters because of interface states in the gate layer stacks, which are simultaneously recharged with the wire under the gate. 35 Therefore, the absolute values of n 3d presented in Fig. 7 can be considered as an upper limit and are systematically lower to a certain extent.…”
Section: à3mentioning
confidence: 96%
“…Up to now, successful n-or p-type doping has already been reported for various III-V semiconductor nanowires, such as InAs, 7,[30][31][32] GaAs, 33,34 or InN nanowires. 35 The doping of InAs nanowires by SA-MOVPE has not been reported, especially at the high growth temperature needed when using an N 2 ambient. Here, we studied the impact of Si doping on the nanowire morphology, structure, and conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…From measurements on nanowires contacted with normal contacts with various distances a specific resistance of ρ = 4.2 × 10 −4 Ωcm was estimated. 19 Using these values we calculated a diffusion constant of D = 110 cm 2 /s.…”
mentioning
confidence: 99%